Mysterious disappearances - Townsend, John, 1955- (Raintree freestyle, 2004)
Examines some of the world's greatest mysteries, looking at reports of people who have disappeared, many never to be seen again, including pilot Amelia Earhart, Australian prime minister Harold Holt, and others.